Evaluation of Health System Preparedness for Post-Disaster Health Crises - Inaya Nur Aini; Isah Fitriani; Ryryn Suryaman Prana Putra (PT. Anagata Sembagi Education, 2026)
Post-disaster health crises frequently expose structural vulnerabilities within health systems, including disrupted service delivery, limited medical resources, and weak inter-institutional coordination. This study aims to evaluate the level of health system preparedness for post-disaster health crises and to identify the structural barriers that hinder effective response and recovery. A mixed-methods approach was employed using a convergent explanatory design. Quantitative data were collected through a health system preparedness checklist covering human resources, infrastructure, logistics, referral systems, and emergency response protocols. Descriptive statistics and gap analysis were used to assess preparedness levels against established standards. Qualitative data were obtained through in-depth interviews with health policymakers, facility managers, and frontline health workers involved in disaster response, and analyzed thematically to explain quantitative findings.The results indicate that overall health system preparedness is at a moderate level, with relatively strong formal preparedness in emergency protocols but substantial gaps in logistics capacity, human resource availability, and operational coordination. Qualitative findings reveal that fragmented governance, delayed resource mobilization, and limited functional integration across institutions undermine the implementation of preparedness plans during post-disaster conditions. The integration of quantitative and qualitative results highlights a persistent gap between formal preparedness and functional readiness.This study concludes that effective post-disaster health preparedness requires moving beyond administrative compliance toward strengthening functional system capacity. The findings underscore the value of mixed-methods evaluation in generating comprehensive evidence to inform policy reforms aimed at improving health system resilience in disaster-prone settings.